Do cross-border mergers and acquisitions create value? Evidence from Chinese firms - Yang, Yadi (2018)
Following the extensive prior studies of the performance in cross-border mergers and acquisitions (M&A), this dissertation tested whether Chinese acquirers can generate value in Chinese outbound mergers and acquisitions and the main factors which might affect the value creation. A sample of 322 outward M&A transactions undertaken by 224 Chinese firms during the period from 2000 to 2017 was examined. The research is based on the event study method and regression analysis. The results show that on average, Chinese overseas M&A can generate a positive excess return for acquirers in short term. The findings of cross-sectional regression analysis present that cash payment exerts a significant positive effect on value creation, while cultural distance, state ownership and industry relatedness fail to make a significant impact on shareholders’ value.